1985
DOI: 10.1021/np50042a025
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the Essential Oils from Two Varieties of Cymbopogon distans

Abstract: Cymbopogon distans (Steud.) Wats. (l), unlike other species of the series Citrati, has linear-to-filiform leaf blades and a shallowly concave lower glume of the sessile spikelet (1). Both of the varieties of C . distam reported in the present investigation grow wild in the Himalayan region. In our earlier communication, we had reported the chemical composition of C . distans (2), a species growing around Nainital. We have now identified its major constituent, Cl,H,40, as a-oxobisabolene. The second chemotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…13 It was suggested that several chemotypes of C. distans essential oils have marker compounds R-oxobisabolene-1 (chemotype I); citral, geraniol, and geranyl acetate (chemotype II); piperitone, limonene, and eudesmanediol (chemotype III); and sesquiterpene alcohol (chemotype IV). 13,14 One more chemotype with chemical marker p-menthol (66.5%) was reported later. 24 For the practical application of the essential oil as a novel repellent, further studies on plant cultivation and essential oil standardization will be needed because the chemical composition of the essential oil varies greatly with the plant population.…”
Section: ' Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…13 It was suggested that several chemotypes of C. distans essential oils have marker compounds R-oxobisabolene-1 (chemotype I); citral, geraniol, and geranyl acetate (chemotype II); piperitone, limonene, and eudesmanediol (chemotype III); and sesquiterpene alcohol (chemotype IV). 13,14 One more chemotype with chemical marker p-menthol (66.5%) was reported later. 24 For the practical application of the essential oil as a novel repellent, further studies on plant cultivation and essential oil standardization will be needed because the chemical composition of the essential oil varies greatly with the plant population.…”
Section: ' Results and Discussionmentioning
confidence: 96%
“…19 The above findings suggest that there are great variations in the chemical composition of essential oil of C. distans. 13,14 In fact, C. distans has been reported to occur in nature in the form of several geographical races. 13 It was suggested that several chemotypes of C. distans essential oils have marker compounds R-oxobisabolene-1 (chemotype I); citral, geraniol, and geranyl acetate (chemotype II); piperitone, limonene, and eudesmanediol (chemotype III); and sesquiterpene alcohol (chemotype IV).…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Regardless of the chemical specificity and processing of chemical information during olfactory and/or gustatory reception, O. nubilalis, a highly polyphagous pest (Caffrey and Worthley, 1927), likely uses individual sesquiterpenes as cues for host plant selection. The sesquiterpene, farnesal (1), an intermediate in the pathway of insect juvenile hormone biosynthesis (Sen and Garvin, 1995;Schooley and Baker, 1985), a pheromone for the pyralid moth, Corcya cephalonica (Zagatti et al, 1987), and a widespread phytochemical (Chamblee et al, 1985;Melkani et al, 1985), was an oviposition deterrent to female O. nubilalis. Farnesol (2), a precursor of juvenile hormone, was a deterrent for O. nubilalis, but also is active as a juvenile hormone mimic (Bowers and Thompson, 1963;Schooley and Baker, 1985) and is a gonadotrophic hormone in some adult insects (Slama, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The components of the essential oils of C. distans differ with growth conditions and geographical locations [ 393 ]. Thus, for example, the essential oil from Munsyari (Uttarakhand) was composed of citral (neral + geranial) (35.0%), geranyl acetate (15.0%), and geraniol (9.5%) [ 122 ]. Similarly, the essential oil cultivated in Pantnagar, Uttarakhand was made up predominantly of geranial (22.8%), neral (16.9%), geraniol (14.8%), and geranyl acetate (19.5%) [ 394 ].…”
Section: The Genus Cymbopogonmentioning
confidence: 99%
“…Similarly, the essential oil cultivated in Pantnagar, Uttarakhand was made up predominantly of geranial (22.8%), neral (16.9%), geraniol (14.8%), and geranyl acetate (19.5%) [ 394 ]. However, the oil from Nainital (Uttarakhand) was dominated by α-oxobisabolene (68%) [ 122 ], while C. distans var. Loharkhet essential oil was rich in the sesquiterpenoids eudesmanediol (34.4%) and 5- epi -7- epi -α-eudesmol (11.2%) [ 395 ].…”
Section: The Genus Cymbopogonmentioning
confidence: 99%